Impacts of Infrastructure Development on African Cape Buffalo Behavior: A Case Study of Lake Nakuru National Park, Nakuru County, Kenya - Ogwoka, Maureen; Koskei, Ednah; Michura, Eliud (KABARAK UNIVERSITY, 2019)
Infrastructure development is a necessary activity; however, if the developers do not consider the environment during the design, planning and construction stages, ecosystem losses are bound to happen. African Cape buffalo behavior alteration is the main challenge caused by the existence of infrastructure in Lake Nakuru National Park. The primary purpose of this study was to assess the effects of infrastructural development on African buffalo behavior in Lake Nakuru National Park. Primary data collection was done using; Key Informant Interviews (KIIs), structured questionnaires and field observation. Secondary data was collected by reviewing government documents, published documents and related documents. Quantitative data was managed using Statistical Package for social science (SPSS). The study sought to recommend strategies to remedy the behavioural changes of the African Cape buffalo triggered by infrastructure existence in Lake Nakuru National Park.
FULL TEXT
Keywords: Infrastructural development, Africa Cape Buffalo behavior.